Building Resilience in Turkey : Quantifying Climate and Disaster Risks to Critical Infrastructure, Lifelines and Agriculture - World Bank (World Bank, Washington, DC, 2020)
The report discusses the methodological steps undertaken to inform the three studies and provides an overview of new approaches and insights for quantifying climate and disaster risks to critical infrastructure, lifelines and agriculture in specific regions and operational units in Turkey. The studies subject to review in this report are considered to be first of their kind in Turkey and are expected to set an example for other institutions to build capacities to deal with various adverse effects of climate change and natural disasters on their key industries, assets and services. The studies are not short of limitations, due to their pilot nature. All three studies aim to provide risk-informed strategic guidance to beneficiary counterparts, rather than detail-oriented and theoretical approaches. All three reports build on probabilistic multi-hazard risk assessments -each risk assessment comprises the following steps: (i) defining and understanding criticality of the assets and products; (ii) understanding vulnerability of critical infrastructure and key assets/products; and (iii) addressing vulnerability. The report further focuses on the Key Agricultural Product Risk Assessment (KAPRA) study. The KAPRA aims to develop financial options to build resilience in Izmir’s agricultural economy and competitiveness by taking into account the effects of climate change and the risks associated with it as well as the sustainability of natural resources and social dynamics. The KAPRA is one of the first in Turkey to look at the effects of climate change on agricultural outputs and to suggest solutions for economically viable climate change adaptation and resilience measures in the agricultural sector. The study was conducted in collaboration with Izmir Development Agency (IZKA). The report explains the framework which was developed in the KAPRA for the concept of ‘key agricultural product’ and then shows how five key agricultural products were chosen for Izmir region, focusing on economic, social and ecological impacts. The report explains in a next step the methodology of the KAPRA for assessing climate change risks through the production chain, focusing on changes in the precipitation regime and in air temperatures, hailstorms, drought events and frost event. The methodology of the risk assessment is showcased with the example of olive oil production. Finally, resilience solutions and business cases which were developed in the KAPRA are presented based on two examples of olive oil production.